Kolaborasi Perguruan Tinggi Dan Masyarakat Dalam Meningkatkan Kesehatan Lingkungan Melalui Praktek Eco Enzyme Dan Biopori Di Desa Suak Lanjut - Sukamarriko Andrikasmi; Agustina Zalukhu; Syahfitri Khairunnisa; Mulia Fitri; Nia Ramadhani Putri; Adelia Gustina; Fitri Utami; Teza Aulia Lubis; Fitri Vani Mardotilla; Arya Ardhana; Ilham At Thariq; Rahma Damena Ginting (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Collaboration between universities and communities plays a crucial role in addressing environmental issues, particularly in the management of organic waste in rural areas. This article presents the results of a community service program by the University of Riau through the Kuliah Kerja Nyata (Kukerta) Tematik Literasi program in Suak Lanjut Village, Siak Regency, Riau. The program aimed to improve environmental health by introducing simple technologies, such as eco enzyme and biopori absorption pits. The method used was a participatory approach combining qualitative and quantitative methods through three stages: The first stage involved field observations, interviews with housewives from the PKK, and an analysis of data from the Siak Regency Environmental Protection Agency (2023), which showed that 67% of waste was organic material. The main activity involved 25 participants and three sessions: a lecture, a demonstration of eco enzyme production, and a practice of biopori creation using plastic bottles. The results showed an increase in environmental awareness. The positive impacts are reduced methane gas emissions, increased production of compost, and eco ezymes that are environmentally friendly. The program aligns with the Tridharma of Higher Education, supports the Siak Green program, and contributes to SDG goals 3 and 12.